Endothelin receptor-A mediates degradation of the glomerular endothelial surface layer via pathologic crosstalk between activated podocytes and glomerular endothelial cells. - Ebefors, Kerstin (Kidney Int, 2019)
Emerging evidence of crosstalk between glomerular cells in pathological settings provide opportunities for novel therapeutic discovery. Here we investigated underlying mechanisms of early events leading to filtration barrier defects of podocyte and glomerular endothelial cell crosstalk in the mouse models of primary podocytopathy (podocyte specific transforming growth factor-β receptor 1 signaling activation) or Adriamycin nephropathy. We found that glomerular endothelial surface layer degradation and albuminuria preceded podocyte foot process effacement. These abnormalities were prevented by endothelin receptor-A antagonism and mitochondrial reactive oxygen species scavenging. Additional studies confirmed increased heparanase and hyaluronoglucosaminidase gene expression in glomerular endothelial cells in response to podocyte-released factors and to endothelin-1. Atomic force microscopy measurements showed a significant reduction in the endothelial surface layer by endothelin-1 and podocyte-released factors, which could be prevented by endothelin receptor-A but not endothelin receptor-B antagonism. Thus, our studies provide evidence of early crosstalk between activated podocytes and glomerular endothelial cells resulting in loss of endothelial surface layer, glomerular endothelial cell injury and albuminuria. Hence, activation of endothelin-1-endothelin receptor-A and mitochondrial reactive oxygen species contribute to the pathogenesis of primary podocytopathies in experimental focal segmental glomerulosclerosis.